Externalities in appropriation: Responses to probabilistic losses - Esther Blanco; Tobias Haller; James M. Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
We examine behavior in one-shot appropriation games with deterministic and probabilistic degradation externalities, where the marginal net benefit from appropriation is endogenous, dependent on individuals' expectations of group appropriation. The experimental design involves a menu of games where the magnitude of a loss parameter associated with probabilistic degradation varies across games. On average, as the loss parameter increases we observe a significant reduction in group appropriation. There is, however, considerable heterogeneity in behavior. First, subjects who are more pessimistic (optimistic) about group appropriation significantly increase (decrease) appropriation as the loss parameter increases. Second, relative to subjects with more optimistic expectations regarding group appropriation, the appropriation of subjects who are more pessimistic is more closely tied to changes in expected marginal benefits.
Keywords: D70; D81; H41; C90; 330; Social dilemma; Laboratory experiment; Endogenous externality; Strategic uncertainty